End-users’ AAL and ELE service scenarios in smart personal environments - Autexier, Serge; Goleva, Rossitza; M Garcia, Nuno; Stainov, Rumen; Ganchev, Ivan; X Mavromoustakis, Constandinos; Dobre, Ciprian; CHorbev, Ivan; Trajkovikj, Vladimir; Zdravevski, Eftim (My University, 2017)
This chapter presents results from ambient assisted living (AAL) and enhanced living environment (ELE) service identification and testing performed within an AAL lab. Possible end-user testing groups and scenarios of ‘AAL as a service’ and ‘ELE as a service’ (ELEaaS) platforms are described and specified. Firstly, protocols and services classifications are presented according to the end-user-specific requirements from communication and information point of view as the chapter aims to show how end-users, caregivers and service providers can be prepared for the challenges of the market. The aim of the test group is to verify and validate the platforms and services for the ELE created, integrated, described and specified. The testing is based on the platform technology and depends on the user requirements’ analysis and ongoing work throughout use-cases. Existing living labs experience has been used and enriched by customized information and communication services known from the information and communication technologies sector. Description of the ELEaaS is done in general terms along with the testing needed to be performed against the general type of provided functionalities. Furthermore, customization of the services, applicability to the needs of all stakeholders, flexibility for data exchange, integration and interoperability between different versions and types of platforms need to be also verified.